A literature review on agility- is there a need to develop a new instrument? - Haider, S. A.; Martins, J. M.; Khan, Soha; Mata, M. N.; Tehseen, Shehnaz *; Abreu, A. (Academy of entrepreneurship, 2021)
The current research provides a review of the literature while contributing to the academic understanding of agility concepts and their backgrounds. The study identified 73 peer reviewed articles on a systematic review process, based on a three-phase purification process. Data reduction processes use combinations, sentence strings, and keyword updates, title, abstract, and conclusion used in the search. The papers identified focused on agility subdomains business, organizational, strategic, and operational agility. The acknowledged gaps in understanding and developing the art and sub-domains have been identified and categorized according to the conceptual, contextual, and practical areas. Apart from that, the findings show that there is a need to develop separate scales for agility sub-domains to achieve, to get better results without having their scale researcher struggle to get the desired results using a simple agility scale. The paper concludes by highlighting the implications for managers, researchers and suggests a number of future research areas.